High level of quinolone resistance in Escherichia coli from healthy chicken broilers - Kmet, V; Kmetová, M (Folia microbiologica, 2010)
The development of resistance to quinolones (nalidixic acid, ciprofloxacin and enrofloxacin) in 2006-2008 was evaluated in 317 strains of Escherichia coli isolated from healthy chicken broilers from various farms. The isolates (2006/2007/2008) showed a high resistance to nalidixic acid (87/85/67 %), ciprofloxacin (CIP) (49/54/29 %) and enrofloxacin (ENR) (52/42/22 %). Nalidixic acid-resistant isolates with low level of MIC for CIP and ENR represented a single mutation; intermediary MIC for CIP and ENR were related to two mutations and high level resistance MIC for CIP (> or =4 mg/L) and ENR (> or =16 mg/L) represented three mutations (two in gyrA and one in parC). There was a correlation between the phenotype reading of high-level resistance and mutations in gyrA (Ser83Leu, Asp87Tyr or Asp87Asn) and parC (Ser80Ile) gene. Plasmid-mediated quinolone-resistance qnrS gene was detected in one Escherichia coli strain with a high level of ciprofloxacin resistance. Our results demonstrate the increase in occurrence of multiresistant E. coli strains with a high level of chromosomal and plasmid resistance to fluoroquinolones.
Keywords: Mutation, Missense; Amino Acid Sequence; Animals; molekulární sekvence - údaje; DNA Topoisomerase IV; Drug Resistance, Bacterial; Chromosomes, Bacterial; Molecular Sequence Data; chinolony; sekvence aminokyselin; Plasmids; DNA-topoisomerasa IV; Amino Acid Substitution; bakteriální chromozomy; Chickens; Escherichia coli Proteins; proteiny z Escherichia coli; Microbial Sensitivity Tests; Anti-Bacterial Agents; zvířata; kur domácí; Quinolones; bakteriální léková rezistence; mikrobiální testy citlivosti; substituce aminokyselin; DNA Gyrase; antibakteriální látky; plazmidy; missense mutace; Escherichia coli; DNA gyráza